Impact of telephonic interviews on persistence and daily adherence to insulin treatment in insulin-naive type 2 diabetes patients: dropout study - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2016)
Objective: The objective of this study is to evaluate the impact of sequential telephonic interviews on treatment persistence and daily adherence to insulin injections among insulin-naive type 2 diabetes patients initiated on different insulin regimens in a 3-month period. Methods: A total of 1,456 insulin-naive patients with type 2 diabetes (mean [standard deviation, SD] age: 56.0 [12.0] years, 49.1% were females) initiated on insulin therapy and consecutively randomized to sequential (n=733) and single (n=723) telephonic interview groups were included. Data on insulin treatment and self-reported blood glucose values were obtained via telephone interview. Logistic regression analysis was performed for factors predicting increased likelihood of persistence and skipping an injection. Results: Overall, 76.8% patients (83.2% in sequential vs 70.3% in single interview group, (P<0.001) remained on insulin treatment at the third month. Significantly higher rate for skipping doses was noted in basal bolus than in other regimens (27.0% vs 15.0% for premixed and 15.8% basal insulin, respectively, P<0.0001). Logistic regression analysis revealed sequential telephonic interview (odds ratio [OR], 1.531; 95% confidence interval [CI], 1.093-2.143; P=0.013), higher hemoglobin A1c levels (OR, 1.090; 95% CI, 0.999-1.189; P=0.049), and less negative appraisal of insulin therapy as significant predictors of higher persistence. Basal bolus regimen (OR, 1.583; 95% CI, 1.011-2.479; P=0.045) and higher hemoglobin A1c levels (OR, 1.114; 95% CI, 1.028-1.207; P=0.008) were the significant predictors of increased likelihood of skipping an injection. Conclusion: Our findings revealed positive influence of sequential telephonic interview, although including no intervention in treatment, on achieving better treatment persistence in type 2 diabetes patients initiating insulin.
Keywords: type 2 diabetes; insulin analogs; HbA1c; self-monitoring of blood glucose; GLYCEMIC CONTROL; OPEN-LABEL; BARRIERS; INITIATION; MANAGEMENT; MULTICENTER; INJECTION; REGIMENS; EFFICACY; THERAPY